Strategy of Islamic Religious Counselors in Increasing the Practice of Worship - Hakiki, Robi Nur; Gumay, Ghiffari Ananda; Setyawati, Rini (Jurnal Dakwah dan Komunikasi, 2023)
The complex problems faced by today's society, especially the Simpang Mutaralam congregation, require adequate competence from the Islamic religious extension program that has been created previously. Judging from the village, there is still minimal opportunity to learn the Koran which is managed by Islamic religious instructors so that A program was formed to increase the practice of worship, there are also other activities that take place, such as rotating yasinan between mothers and fathers, making sacrifices every year, but it has been emphasized by Islamic religious instructors that this is a priority problem in the village, namely eradicating illiteracy in the practice of worship in the community. Simpang Mutar Alam itself. The aim of the research was to determine the strategies of Islamic religious instructors in improving the worship experience of the people of Simpang Mutaralam Pekon Mutar Alam, Way Tenong District. The research method used is field research with a qualitative descriptive nature. The results of this research are: the strategy prepared by the KUA Islamic Religious Counselor in Way Tenong District through the planning, implementation and evaluation stages, a) Planning, the strategy used by the instructor, namely through a heart-to-heart approach, b) Implementation, the strategy used by extension workers by providing good advice or direction to the people of Simpang Mutaralam, c) Evaluation, carried out once a month using observations, interviews and work meetings.